Narratives of the caves of Kumbe Mayo-Peru - López Aldave, Natali (2021)
In this article, five caves found at ceremonial center of Kumbe Mayo, located in the department of Cajamarca, Perú, are analyzed. This study is based on spatial and iconographic analyses, as well as a review of historical and ethnographic sources. The symbols found at Kumbe Mayo revolve around, as seen materialized in the construction of the canal, narratives related to the sacredness of water, space-time, ancestors, and fertility. Furthermore, in the figures embodied in the caves, zoomorphic, geometric and anthropomorphic symbols are prevalent. These narratives extend to other sites in the central Andes and Mexico.